An audit of healthcare provision in internally displaced population camps in Nigeria - Ekezie, Winifred; Timmons, Stephen; Myles, Puja; Siebert, Penelope; Bains, Manpreet; Pritchard, Catherine (Oxford University Press, 2018)
Background: Armed conflict in Nigeria resulted in more than 2 million internally displaced persons (IDPs). IDPs live in poor conditions lacking basic resources with variable provision across different locations. This audit aimed to determine the health-related resources available to IDPs in camp-like settings in Nigeria and whether these met international standards. Methods: Using a cross-sectional study approach, information was collected in 9 camps across 7 states from camp managers, and direct observation in September-October 2016. The Sphere minimum standards in humanitarian crises were used as the audit standards. Findings: Five of 15 assessed standards were met to some extent, including the availability of water and shelter. Sanitation and vaccination were unmet in 5 camps, with severe overcrowding in 5 camps, and inadequate waste disposal in all camps. Health programme implementation was uneven, and especially poor in self-settled and dispersed settlements. Conclusion: Inequality in distribution of humanitarian support was observed across different settings, which could lead to a higher likelihood of water, food and air related diseases and thereby, a poorer quality of life for IDPs. Ensuring standardised health assessments could promote a more even distribution of resources across IDP locations.